Socio-Economic Inequalities in Tobacco Consumption of the Older Adults in China: A Decomposition Method - Yafei Si; Zhongliang Zhou; Min Su; Xiao Wang; Dan Li; Dan Wang; Shuyi He; Zihan Hong; Xi Chen (Institute of Labor Economics (IZA), 2018)
In China, tobacco consumption is a leading risk factor for non-communicable diseases, and understanding the pattern of socio-economic inequalities of tobacco consumption will, thus, help to develop targeted policies of public health control. Data came from the China Health and Retirement Longitudinal Study in 2013, involving 17,663 respondents aged 45 and above. Tobacco use prevalence and tobacco use quantities were defined for further analysis. Using the concentration index (CI) and its decomposition, socio-economic inequalities of tobacco consumption grouped by gender were estimated. The concentration index of tobacco use prevalence was 0.044 (men 0.041; women -0.039). The concentration index of tobacco use quantities among smokers was 0.039 (men 0.033; women 0.038). The majority of the inequality could be explained by educational attainment, age, area, and economic quantiles. Tobacco consumption was more common among richer compared to poorer people in China. Gender, educational attainments, age, areas, and economic quantiles were strong predictors of tobacco consumption in China. Public health policies need to be targeted towards men in higher economic quantiles with lower educational attainment, and divorced or widowed women, especially in urban areas of China.
Keywords: I12; I14; J14; 330; tobacco consumption; inequality; concentration index; decomposition; China